Penerapan Model Pembelajaran Aktif Inovatif Kreatif Dan Menyenangkan Untuk Meningkatkan Hasil Belajar Siswa - Heru Widoyo; Agus Rofi’i; Andi Sahtiani Jahrir; Rasimin Rasimin; MS Viktor Purhanudin; Joni Wilson Sitopu (Departement of Mathematics Education, 2023)
This research is a Classroom Action Research (PTK) which consists of Pre-cycle, Cycle I, Cycle II and Cycle III. The purpose of this study was to determine the application of the PAIKEM model can improve student learning outcomes. Each consists of planning, implementation, evaluation and reflection. Learning outcome data obtained by using tests. Analysis of the mastery test of learning outcomes in the pre-cycle reached 26.67%, in the first cycle it reached 53.33%, in the second cycle it reached 60% and in the third cycle it reached 73.33%. Based on the percentage in cycle III it can be said that it has achieved classical learning mastery. The results of the data analysis show that the application of the PAIKEM model can improve student learning outcomes. Based on the results of this research, it is suggested to the teacher that the application of the learning model is applied as an innovation in the teaching and learning process.